2011
DOI: 10.1016/j.neuroimage.2011.02.015
|View full text |Cite
|
Sign up to set email alerts
|

How specific is specific phobia? Different neural response patterns in two subtypes of specific phobia

Abstract: Specific phobia of the animal subtype has been employed as a model disorder exploring the neurocircuitry of anxiety disorders, but evidence is lacking whether the detected neural response pattern accounts for all animal subtypes, nor across other phobia subtypes. The present study aimed at directly comparing two subtypes of specific phobia: snake phobia (SP) representing the animal, and dental phobia (DP) representing the blood-injection-injury subtype. Using functional magnetic resonance imaging (fMRI), brain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
79
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 85 publications
(86 citation statements)
references
References 42 publications
6
79
1
Order By: Relevance
“…Increased activation was found in brain regions that were previously suggested to play a role in anticipation of phobia-specific stimuli in spider phobia (Münsterkötter et al, 2015, Straube et al, 2007). This stands in contrast to studies on phobia-specific picture processing, which found similar (Caseras et al, 2010b) but also distinct brain activations (Caseras et al, 2010a, Lueken et al, 2011) for animal phobia in comparison to BII phobia. Taken together, these findings suggest that diagnostic classifications for specific phobia are meaningful for emotional processing during confrontation with phobia-specific stimuli, but that anticipatory anxiety could be a common denominator among specific phobia subtypes.…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…Increased activation was found in brain regions that were previously suggested to play a role in anticipation of phobia-specific stimuli in spider phobia (Münsterkötter et al, 2015, Straube et al, 2007). This stands in contrast to studies on phobia-specific picture processing, which found similar (Caseras et al, 2010b) but also distinct brain activations (Caseras et al, 2010a, Lueken et al, 2011) for animal phobia in comparison to BII phobia. Taken together, these findings suggest that diagnostic classifications for specific phobia are meaningful for emotional processing during confrontation with phobia-specific stimuli, but that anticipatory anxiety could be a common denominator among specific phobia subtypes.…”
Section: Discussioncontrasting
confidence: 99%
“…The current fMRI results support this assumption, as findings replicate activation patterns previously shown for anticipatory anxiety in spider phobia (Münsterkötter et al, 2015, Straube et al, 2007), social anxiety disorder (Boehme et al, 2014, Lorberbaum et al, 2004) and panic disorder (Boshuisen et al, 2002, Wittmann et al, 2014). This is especially interesting in the light of fMRI studies that investigated confrontation with phobia-relevant stimuli in BII phobia which suggest inconclusive and unspecific results (Caseras et al, 2010a, Caseras et al, 2010b, Hermann et al, 2007, Lueken et al, 2011, Schienle et al, 2003). More specifically, direct comparison between BII and animal phobics showed distinct neural substrates for the two subtypes (Caseras et al, 2010a, Caseras et al, 2010b, Lueken et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Emotional responses like fear and anxiety are grounded in 'complex systems' that feed back to sensory systems, heightening vigilance and information gathering (if a threat is expected or detected) and, importantly, prompting for example defensive reflexive, autonomic, and motor responses that in evolutionary history acted directly to counter threats and escape punishments [Arch and Craske, 2009]. Comparative research across different forms of mental disorders is necessary to detect such core aspects of dysfunctions shared by all disorders in contrast to disorder-specific features [Etkin and Wager, 2007;Haber and Rauch, 2010;Lueken et al, 2011;Domschke and Deckert, 2012] and to inform how therapeutic interventions can be optimized, e.g. by component, mediator and moderator analyses.…”
Section: Identifying Core Ingredients and Mechanisms Of Actionmentioning
confidence: 99%